Indirect somatic embryogenesis and plant regeneration through leaf and nodal cultures of Piper longum L. - Thapa, Chandra Bahadur; Pant, Krishna Kumar; Bhattarai, Hari Datta; Pant, Bijaya (Banko Janakari, 2024)
This research aims to develop a protocol for inducing somatic embryogenesis and plant regeneration through callus in Piper longum. Leaf and nodal explants were cultured in the Murashige and Skoog medium added with 2, 4-dichlorophenoxyacetic acid (2, 4-D) or α-naphthaleneacetic acid (NAA), Kinetin (KN), and 10% coconut water (CW). The maximum frequency of embryogenic/nodular callus development (66.66%) and the number of embryos (28.33±3.511) per 0.2-0.3 g embryogenic callus developed from the leaf explant was obtained in the MS + 1.5 mg/L 2, 4-D + 1.0 mg/L KN + 10% CW. Similarly, the maximum frequency of embryogenic/nodular callus production (50%) and the number of embryos (12.66±2.51) per 0.2-0.3 g embryogenic callus developed from the stem explant were obtained in the MS + 1.0 mg/L NAA + 10% CW. Somatic embryo differentiation, maturation, and conversion were obtained when the nodular calli with various stages of embryos were transferred to the MS + 0.25 -1.5 mg/L thidiazuron + 10% CW. Somatic embryos were also transformed into seedlings after being transplanted to the MS medium with no growth regulators. This study developed a technique for micropropagation of P. longum using somatic embryos derived from leaf and nodal explants, which could serve as the foundation for an alternate method of micropropagation and ex-situ germplasm conservation.